2017
DOI: 10.1007/s00464-017-5660-4
|View full text |Cite
|
Sign up to set email alerts
|

A standardized comparison of peri-operative complications after minimally invasive esophagectomy: Ivor Lewis versus McKeown

Abstract: In this cohort, totally MIE IL showed significantly less severe peri-operative morbidity than MIE 3-hole, but similar rates of serious pulmonary complications and anastomotic leaks. These findings confirm the safety of minimally invasive Ivor Lewis esophagectomies for esophageal cancer when oncologically and clinically appropriate. Minimally invasive McKeown esophagectomy remains a satisfactory and appropriate option when clinically indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 28 publications
2
28
1
Order By: Relevance
“…Luketich et al 9 as well as Brown et al 10 reported an anastomotic leak that needed surgery (CD grade ≥3). These reports suggest that anastomotic leak requires surgical or endoscopic intervention, 29 so we pooled these data and found that the incidence of severe anastomotic leak was not significantly different (OR =1.28, 95% CI =0.73–2.24, P =0.39), as shown in Figure 4 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Luketich et al 9 as well as Brown et al 10 reported an anastomotic leak that needed surgery (CD grade ≥3). These reports suggest that anastomotic leak requires surgical or endoscopic intervention, 29 so we pooled these data and found that the incidence of severe anastomotic leak was not significantly different (OR =1.28, 95% CI =0.73–2.24, P =0.39), as shown in Figure 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 3,468 patients from 14 cohort studies underwent totally minimally invasive McKeown or Ivor Lewis esophagectomy were subjected to this meta-analysis. 9 , 10 , 17 28 No randomized controlled studies or studies adopting hybrid MIE were found. Major characteristics and NOS quality star of the included studies are summarized in Tables 1 and 2 (surgical details and other outcomes can be found in Supplementary materials).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Methods to reduce the risk of surgery and postoperative complications 3,4 and to improve the thoroughness of the operation remain controversial. 5,6 The number of lymph nodes dissected is one of the most important indexes to evaluate the thoroughness of EC surgery, which is closely related to the total survival of patients. 7,8 Because of the disadvantages of lymph node dissection, the use of Sweet surgery has gradually been reduced.…”
Section: Discussionmentioning
confidence: 99%